Analysis of Determining Production Cost Using the Activity-Based Costing (ABC) Method at Putra Mandiri Mebel - Nuralifah Alawiah; Rio Monoarfa; Mentari R. Sawitri Pilomonu (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the determination of production cost using the Activity-Based Costing (ABC) method at Putra Mandiri Mebel. The Activity-Based Costing method was chosen because it is capable of calculating costs more accurately in manufacturing companies by allocating costs based on the activities consumed in the production process—from the beginning through to the finished goods stage—in a more specific manner compared to conventional methods. With this method, the cost of goods manufactured can be calculated more precisely based on the activities consumed by the product. This study employs a qualitative descriptive approach using data collection techniques such as document analysis and interviews. The results of this study indicate a difference in calculations between the conventional method and the Activity-Based Costing (ABC) method. For sofa products, overcosting occurred, where the conventional method estimated the COGS for the sofa at Rp 32,285,105, and the COGS for teak chairs at Rp 40,583,731. Meanwhile, the estimated COGS for products using the ABC strategy at Putra Mandiri Mebel resulted in Rp 26,865,102 for sofas and Rp 35,807,447 for teak chairs. This study recommends that the company adopt Activity-Based Costing (ABC) to review its cost calculation methods when determining COGS.